Germinal center B-cells resist transformation by Kras independently of tumor suppressor Arf. - Chelsea D Mullins; Mack Y Su; Vishwanathan Hucthagowder; Liang Chu; Lan Lu; Shashikant Kulkarni; Deborah Novack; Ravi Vij; Michael H Tomasson (PLoS ONE, 2013)
Activating mutations in Ras (N- and K-) are the most common point mutations found in patients with multiple myeloma (MM) and are associated with poor clinical outcome. We sought to directly examine the role of Ras activation in MM pathogenesis and used two different tissue-specific Cre recombinase mouse lines (Cγ1-Cre and AID-Cre), to generate mice with mutant Kras (Kras(G12D) ) activated specifically in germinal center B-cells. We also generated mice with activation of the Kras(G12D) allele in a tumor-prone Arf-null genetic background. Surprisingly, we observed no significant disruption in B-cell homeostasis in any of these models by serum immunoglobulin ELISA, SPEP, flow cytometry and histological examination. We observed development of non-overlapping tumor types due to off-target Cre expression, but despite successful recombination in germinal center and later B-cell populations, we observed no B-cell phenotype. Together, these data demonstrate that Ras activation is not sufficient to transform primary germinal center B-cells, even in an Arf-null context, and that the temporal order of mutation acquisition may be critical for myeloma development. Specific pathways, yet to be identified, are required before Kras can contribute to the development of MM.